Produktywność środków trwałych i czynniki ją kształtujące w przemyśle spożywczym - Sobolewski, Henryk (Wydział Prawa i Administracji UAM, 1979)
The aim of the article is recognition and evaluation of general regularities in the fixed capital productivity shaping as well as recognition and analysis of factors influencing it's level and dynamics. The methods of total and partial correlations, along with tabular and verbal analyses, were of service in examination of factors influence on level and dynamics of the fixed capital productivity. The research carried out showed that the fixed capital productivity was determined mainly by level of utilization of fixed capital, which was expressed by indicators of productive utilization of machines and technical equipment working time, indicators of utilizing production capacity and shift rotation. Other factors influenced the fixed capital productivity in much weaker way. If relation compactness was accepted as a basis the sequence of other factors would be as follows: structure of fixed capital according to executed functions, employment; structure, degree of production renovation, quality of produced ready-made products.
The Fixed Capital Productivity and It's Shaping Factors in the Foodstuff Industry